No growth without equity? : (World Bank, 2009)
No Growth without Equity? Inequality, Interests, and Competition in Mexico presents a novel analysis showing why more equality is necessary to increase economic growth. The authors analyze the causes of persistent inequality and weak growth in Mexico, despite major changes associated with NAFTA and democratization, and draw implications for policy design. The book involves an innovative synthesis of work on overall links between equity and growth, and carefully grounded analysis in specific areas. The issues are of intense interest to policy debate in Mexico and to the development community in Latin America and elsewhere.